Health care for poor people in the urban slums of Bangladesh - Afsana, Kaosar; Wahid, Syed Shabab (© 2013 The Lancet, 2017)
This note was published in The Lancet [© 2013 The Lancet] and the definite version is available at: http://www.thelancet.com/journals/lancet/article/PIIS0140-6736(13)62295-3/abstract